Perceived athletic and academic stressors and time management of student athletes - Miller, A.; Chen, S. S.; Chiu, T.-C. (ASAHPERD, 2018)
The purpose of this study is to examine how student-athletes perceive daily stresses derived from their athletic, academic, and social obligations. In addition, the authors investigated the student-athletes` time management and the support they expect to receive in order to cope with stress. The results of the study will help the administrators and faculty members learn about student-athletes` daily activities and their psychological states, which should help them aid and improve the well-being of the student-athletes.